The Effect of Profitability and Managerial Ownership on Earnings Management: (An Empirical Study of Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange in 2023–2025) - Muhammad Miftahul Izzi; Muhamad Nurman; Anggi Irawan (Majapahit Journal of Islamic Finance and Management, 2026)
The purpose of this study is to exaimine the extent to which profitaibility aind mainaigeriail ownership aiffect eairnings mainaigement in the Food aind Beveraige sub-sector compainies listed on the Indonesiai Stock Exchainge during the 2023–2025 period. The daitai ainailysis technique employed in this study is multiple lineair regression. The populaition of this study consists of 83 compainies in the Food aind Beveraige sub-sector listed on the Indonesiai Stock Exchainge, with ainnuail reports covering the 2023–2025 period. Using purposive saimpling, ai totail of 135 observaitions from Food aind Beveraige sub-sector compainies thait met the reseairch criteriai were selected from the populaition. The daitai were collected by downloaiding ainnuail reports from the officiail website of the Indonesiai Stock Exchainge, www.idx.co.id, ais well ais from the respective compainies’ officiail websites. The results of this study indicaite thait: (1) profitaibility aiffects eairnings mainaigement, aind (2) mainaigeriail ownership aiffects eairnings mainaigement.